Pendekatan Restoratif Dalam Keluarga; Upaya Melindungi Hak-Hak Istri dan Anak Pasca-Perceraian Tinjauan Hukum Keluarga Islam di Indonesia - Achmad Suhaili; Iklilhasbiyalla (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
This study examines the integration of the restorative approach within Islamic family law in Indonesia as an effort to strengthen the protection of the rights of wives and children after divorce. This research employs a qualitative normative method with a descriptive-analytical approach by examining the principles of classical Islamic law, Islamic family law in Indonesia, and the restorative concept as an alternative approach to resolving family conflicts. The findings indicate that restorative values are aligned with the principles of justice, balance, and public welfare (maṣlaḥah) in classical Islamic law and have been partially accommodated in the practice of Islamic family law in Indonesia through the role of the Religious Courts and the Compilation of Islamic Law (KHI), although significant implementation challenges remain. This study implies the importance of strengthening collaboration among judges, Islamic scholars, and family counselors, as well as optimizing mediation based on Sharia values, to achieve divorce resolution processes that are more just, harmonious, and oriented toward the best interests of the child. Keywords: Restorative Approach, Protection of Wives’ and Children’s Rights, Post-Divorce, Islamic Family Law